Corrected T(q)-Likelihood Estimator in a Generalized Linear Structural Regression Model with Measurement Errors - Savchenko, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study a generalized linear structural regression model with measurement errors. The dispersion parameter is assumed to be known. The corrected T (q) -likelihood estimator for the regression coefficients is constructed. In the case where q depends on the sample size and approaches 1 as the sample size infinitely increases, we establish sufficient conditions or the strong consistency and asymptotic normality of the estimator.